WHO DO WE TALK TO ABOUT AGE-RELATED PLANNING? MAPPING CONVERSATION PARTNERS TO UNDERSTAND PATTERNS AND OVERLAP. (11th November 2018) - Chen, E; Kennedy, D
Abstract: Research on advanced care planning (ACP) – plans that express or document wishes for health care for when a person is not able to communicate their decisions - has often conceptualized ACP as a health behavior. However, research shows that individuals understand ACP as just one of a larger set of things that they do to plan for late life. We first present a conceptual framework – an extension of Kahana and colleagues' Proactivity Model of Successful Aging – that situates ACP within a broader context of age-related planning, such as financial planning for retirement, estate planning, and plans for residential changes. Next, based on this framework, and using the open-source EgoWeb software, we describe the interactive interview activity that we developed to elicit and visualize information about age-related planning conversations. The interview protocol focuses on whom people talk to about what types of planning and the characteristics of these conversations and conversation partners. Throughout the interview, responses are coded and displayed in an interactive "hub and spokes" graphic which is used as a prompt to elicit respondents' explanations of and reactions to their planning conversation network, such as how or why conversations on some topics occurred but not on others. Understanding ACP conversations and conversation partners in the context of other types of age-related planning conversations could provide important entry points for interventions, such as targeting typical conversation partners to help initiate these difficult conversations, or suggesting segues to ACP from more common or co-occurring topics, like financial planning.